Experimental Investigation of the Effect of Curvature Ratio on Heat Transfer in Double Pipe Helical Heat Exchanger - Hoshi, Hisham Assi (Al-Khwarizmi Engineering Journal, 2018)
Different parameters of double pipe helical coil were investigation experimentally. Four coils were used; three with a curvature ratio (0.037, 0.031, and 0.028) and 11mm diameter of the inner tube while the fourth with 0.033 curvature ratio and 13 mm diameter of the inner tube. The hot water flow in the inner tube whereas the cold water flows in the annulus. The inlet temperatures of hot and cold water are 50 0C and 18 0C respectively. The inner mass flow rate ranges from 0.0167 to 0.0583 kg/s. The results show the Nusselt number increase with increase curvature ratio. The Nusselt number of the coil with 0.037 curvature ratio increases by approximately 12.3 % as compare with 0.028 curvature ratio. The results also reveal that the Nusselt number of the coil with curvature ratio 0.033 increases by approximately 11.6 % as compare with 0.028 curvature ratio for 400 mm coil diameter.